Badania nad Przepływem Poddźwiękowym Płynu Ściśliwego w Kanale w Obecności Przeszkody - Popp, S. (Engineering Transactions, 1965)
This is an analysis of a steady-state plane subsonic flow with no rotation of a compressible fluid through duct with parallel walls and an almost circular obstacle. The authoress confronts her results obtained in some previous works with those obtained by other authors. Very good agreement has been found.